Synthesis and characterization of Ba0.5Sr0.5Co0.8Fe0.1Ni0.1O3-δ cathode for intermediate-temperature solid oxide fuel cells. (29th March 2018) - Wang, Biao; Long, Guohui; Li, Yunfei; Jia, Hongbao; Qiu, Dongchao; Wang, Jian; Liu, Gaobin; Wang, Kaiming; Ji, Yuan
Abstract: Perovskite Ba0.5 Sr0.5 Co0.8 Fe0.1 Ni0.1 O3-δ (BSCFNi) oxide is synthesized and characterized as a cathode material for intermediate-temperature solid oxide fuel cells (IT-SOFCs). The X-ray diffraction (XRD) spectra show that BSCFNi is chemical compatible with La0.9 Sr0.1 Ga0.83 Mg0.17 O2.865 (LSGM) electrolyte below 950 °C, but weak reaction is observed between BSCFNi cathode and Sm0.2 Ce0.8 O1.9 (SDC) electrolyte after calcined at 950 °C for 10 h. The XPS results indicate that transition metal cations in BSCFNi sample exist two different valence states, i.e., Co 4+/3+, Fe 4+/3+ and Ni 3+/2+ . The average thermal expansion coefficient (TEC) of BSCFNi is 18.7 × 10 −6  K −1 between 200 °C and 850 °C in air. The maximum electrical conductivity reaches 35.3 Scm −1 at 425 °C in air. The polarization resistance of BSCFNi cathode on LSGM and SDC electrolytes are 0.033 and 0.066 Ωcm 2 at 800 °C, respectively. The maximum power density of LSGM electrolyte-supported single cell with BSCFNi cathode reaches 690 mWcm −2 at 800 °C. These primarily results indicate that BSCFNi is a candidate cathode material for IT-SOFCs. Highlights: Perovskite Ba0.5 Sr0.5 Co0.8 Fe0.1 Ni0.1 O3-δ is firstly investigated as SOFC's cathode. Mixed valence state of Co 4+ /Co 3+, Fe 4+ /Fe 3+ and Ni 3+ /Ni 2+ in the cathode sample. Cathode has good chemical compatibility with La0.9 Sr0.1 Ga0.83 Mg0.17 O2 below 950 °C. The partial substitution of Ni for Fe can lower the TEC of the cathode. Low area specific resistance and high power density on LSGM electrolyte are obtained.